Bridging the gap: assessing CMV DNAemia in kidney transplant recipients with previous solid organ transplants - Katz-Greenberg, Goni; Steinbrink, Julie M.; Shah, Krishna; Byrns, Jennifer S. (Frontiers in Transplantation, 2024)
Cytomegalovirus (CMV) infection poses a significant threat to solid organ transplant (SOT) recipients and can lead to various complications and adverse outcomes. In an effort to prevent CMV infection, it is common to utilize prophylactic strategies, including antiviral medications such as valganciclovir, especially for high-risk patients. Risk factors for CMV infection in kidney transplant recipients (KTRs) include CMV mismatch between donor and recipient (i.e., donor positive, recipient negative), and intensity of immunosuppression, such as the use of T-cell depleting agents. However, little attention has been given to KTRs with a history of prior SOTs, despite their prolonged exposure to immunosuppressive regimens. The aim of this retrospective single-center study was to investigate the incidence and implications of CMV DNAemia in KTRs with prior SOTs. The study included 97 KTRs with prior SOTs and 154 KTRs with no prior transplants as a control group. In the study group, the most common SOT before the current kidney transplantation (KT), was a previous KT. Patients in the KTR group with prior SOTs were more sensitized than those in the control group [calculated panel-reactive antibody > 30%: 49 (50.5%) vs. 30 (19.45%) patients, p = 0.001]. There was a 39.2% incidence of CMV DNAemia in the previous SOT group compared to 48.7% in the control group [non-significant (NS)]. Patients with prior SOTs demonstrated a shorter post-transplant time to CMV DNAemia [median time 1.6 months (interquartile range, IQR 0.7–5.8) in the KTRs with prior SOTs vs. 2.6 months (IQR 1.5–8.1) in the control group (p = 0.001)]. Although the study highlights the need for tailored prophylaxis strategies and vigilant monitoring in KTRs with prior SOTs, its limitations, such as its retrospective nature and single-center design, call for further multicenter research to establish comprehensive guidelines for managing CMV DNAemia in this unique patient population. Despite these limitations, this study underscores the importance of recognizing the heightened risk of CMV infection or reactivation in KTRs overall and the potential benefits of proactive intervention to mitigate associated morbidity and mortality.